Functional diversity of microglia – how heterogeneous are they to begin with? - Hanisch, Uwe-Karsten (Frontiers in Cellular Neuroscience, 2013)
Microglia serve in the surveillance and maintenance, protection and restoration of the CNS homeostasis. By their parenchymal location they differ from other CNS-associated myeloid cells, and by origin as well as functional characteristics they are also‒at least in part‒distinct from extraneural tissue macrophages. Nevertheless, microglia themselves may not comprise a uniform cell type. CNS regions vary by cellular and chemical composition, including white matter (myelin) content, blood-brain barrier properties or prevaling neurotransmitters. Such a micromilieu could instruct as well as require local adaptions of microglial features. Yet even cells within circumscribed populations may reveal some specialization by subtypes, regarding house-keeping duties and functional capacities upon challenges. While diversity of reactive phenotypes has been established still little is known as to whether all activated cells would respond with the same program of induced genes and functions or whether responder subsets have individual contributions. Preferential synthesis of a key cytokine could asign a master control to certain cells among a pool of activated microglia. Critical functions could be sequestered to discrete microglial subtypes in order to avoid interference, such as clearance of endogeneous material and presentation of antigens. Indeed, several and especially a number of recent studies provide evidence for the constitutive and reactive heterogeneity of microglia by and within CNS regions. While such a principle of ‘division of labor’ would influence the basic notion of ‘the’ microglia, it could come with the practival value of addressing separate microglia types in experimental and therapeutic manipulations.